The role of the learner in the construction of meaning at Tate Britain - Arriaga, Amaia; Aguirre, Imanol (Arte, Individuo y Sociedad, 2013)
The debates on the interpretation of art that developed in the field of art theory and criticism beginning in the 1960s have influenced the theory and practice of museum education and questioned traditional practices. As a consequence, in recent years, there has been a radical redefinition of the role the viewer must play in interpreting works and exhibitions. The article discusses how and to what extent this turn towards visitor/learner agency in the interpretation has affected educational discourses and practices at Tate Britain gallery. This study is part of a wider investigation analysing how different agents involved in school programmes at Tate Britain conceive of art and interpretation.